2022
DOI: 10.3389/fmed.2022.1013378
|View full text |Cite
|
Sign up to set email alerts
|

A case series of dermatomyositis following SARS-CoV-2 vaccination

Abstract: Background/ObjectiveThe most significant adverse events following SARS-CoV-2 vaccination are myocarditis and pericarditis. Myositis and dermatomyositis have been reported following SARS-CoV-2 infection, but vaccine-induced dermatomyositis (DM) has not been reported. Our case series aimed to characterize new onset dermatomyositis or disease-related flares following SARS-CoV-2 vaccination.Materials and methodsA total of 53 patients from our institution with a new or pre-existing diagnosis of DM were recruited an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
14
0
2
Order By: Relevance
“…SC2V-related cerebrovascular diseases include VST, ischemic stroke, ICH, SAB, pituitary apoplexy, RCVS, cerebral vasculitis, and Susac syndrome ( Table 2 ) [ 4 , 6 …”
Section: Resultsmentioning
confidence: 99%
“…SC2V-related cerebrovascular diseases include VST, ischemic stroke, ICH, SAB, pituitary apoplexy, RCVS, cerebral vasculitis, and Susac syndrome ( Table 2 ) [ 4 , 6 …”
Section: Resultsmentioning
confidence: 99%
“…15 A cohort from Chan et al showed that, of 53 patients diagnosed with DM, 5 presented with symptoms after vaccination. 16 Other studies have seen a correlation between the vaccine and positivity of anti-MDA5 antibodies. 17,18 We performed a retrospective review in our institution to define the frequency of incident DM or a DM relapse following SARS-CoV-2 infection or COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 93%
“…The main autoantibodies found were anti‐TIF‐1‐γ, anti‐SRP, anti‐NXP‐2, anti‐Mi‐2, and anti‐Pm‐Scl 15 . A cohort from Chan et al showed that, of 53 patients diagnosed with DM, 5 presented with symptoms after vaccination 16 . Other studies have seen a correlation between the vaccine and positivity of anti‐MDA5 antibodies 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding SARS-CoV-2-induced IIM are lacking. Review of the literature yields mostly single case reports (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) , with larger case series referring to SARS-CoV-2 vaccines (21,22). Certainly, higher-level evidence is still required to discern whether the incidence of IIM has increased during the pandemic and whether the disease pattern and course have changed.…”
Section: Infectious Diseases Have Long Been Linked To the Development...mentioning
confidence: 99%